Clarithromycin prevents human respiratory syncytial virus-induced airway epithelial responses by modulating activation of interferon regulatory factor-3. (September 2016) - Yamamoto, Keisuke; Yamamoto, Soh; Ogasawara, Noriko; Takano, Kenichi; Shiraishi, Tsukasa; Sato, Toyotaka; Miyata, Ryo; Kakuki, Takuya; Kamekura, Ryuta; Kojima, Takashi; Tsutsumi, Hiroyuki; Himi, Tetsuo; et al.
Graphical abstract: Abstract: Macrolide antibiotics exert immunomodulatory activity by reducing pro-inflammatory cytokine production by airway epithelial cells, fibroblasts, vascular endothelial cells, and immune cells. However, the underlying mechanism of action remains unclear. Here, we examined the effect of clarithromycin (CAM) on pro-inflammatory cytokine production, including interferons (IFNs), by primary human nasal epithelial cells and lung epithelial cell lines (A549 and BEAS-2B cells) after stimulation by Toll-like receptor (TLR) and RIG-I-like receptor (RLR) agonists and after infection by human respiratory syncytial virus (RSV). CAM treatment led to a significant reduction in poly I:C- and RSV-mediated IL-8, CCL5, IFN-β and -λ production. Furthermore, IFN-β promoter activity (activated by poly I:C and RSV infection) was significantly reduced after treatment with CAM. CAM also inhibited IRF-3 dimerization and subsequent translocation to the nucleus. We conclude that CAM acts a crucial modulator of the innate immune response, particularly IFN production, by modulating IRF-3 dimerization and subsequent translocation to the nucleus of airway epithelial cells. This newly identified immunomodulatory action of CAM will facilitate the discovery of new macrolides with an anti-inflammatory role.